Lovemark effect: Analysis of the differences between students and graduates in a love brand study at a public university [L'effet « lovemark »: Une analyse des différences entre les étudiants et les diplômés dans une étude d'une « marque d'amour » dans une université publique] [Efeito lovemark: Análise das diferenças entre estudantes e graduados em um estudo de amor pelas marcas realizado em uma universidade pública] [Efecto lovemark: Análisis de las diferencias entre estudiantes y egresados en un estudio de marca de amor en una universidad pública] (2019)
The purpose of this paper is to consolidate the measurement of a lovemark and unify a set of elements that form a lovemark in university institutions by considering the differences between students and graduates. Based on a review of factors that build a lovemark, brand loyalty relationships were explored. In addition, an empirical study was carried out and applied to a sample of 257 participants at the National University of Colombia (unal), one of the most important universities in this country. The results validated the positive effects of brand love, brand experience, and brand involvement on brand loyalty, the determining factor of a university lovemark. This article is one of the first works integrating all the constructs proposed by prior research studies, which, until now, have approached lovemark and brand loyalty separately. © 2019, Universidad Nacional de Colombia. All rights reserved.